Anxiety, financial stress, and childhood trauma are associated with psychotic-like experiences during the postpartum period - Grattan, Rebecca E.; London, Sophie; Hammond, Matthew D. (Frontiers in Psychiatry, 2025)
PurposePsychotic-like experiences (subclinical psychosis symptoms) predict the development of severe mental distress in the general population and can also be an experience of clinical concern. Little attention has been paid to psychotic-like experiences occurring for women during the postpartum period, despite it being a time of elevated mental distress. In particular, it is unknown how these symptoms present across the postpartum period and what risk factors are associated with them.MethodsThe present study examined psychotic-like experiences across two time points, 4 weeks apart, during the first 6 months postpartum. The prevalence of psychotic-like experiences and the relative change over time were examined, including common risk factors for psychotic-like experiences outside the postpartum period. The included risk factors were history of childhood trauma, birth trauma, depression, anxiety, financial stress, postpartum stress, and sleep difficulties. Social support was also included as a possible protective factor.ResultsPsychotic-like experiences were generally prevalent and persistent over time in the postpartum period and were associated with distress. Anxiety symptoms, financial stress, and history of childhood trauma were associated with psychotic-like experiences cross-sectionally. There was no evidence that any commonly understood risk factors accounted for the change in psychotic-like experiences over 4 weeks.ConclusionsThese findings indicate that stress and anxiety may contribute to the development of postpartum psychotic-like experiences, but it is unclear what factors may lead to worsening symptoms over time.